2018
DOI: 10.1248/bpb.b18-00156
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind, Crossover Clinical Trial of the Effect of Calcium Alginate in Noodles on Postprandial Blood Glucose Level

Abstract: We conducted a prospective, randomized, double-blind, 3-group, 3-phase crossover study to evaluate the effect of calcium alginate (Ca-Alg) on the postprandial increase of blood glucose in 15 healthy adult subjects who were given udon noodles containing or not containing Ca-Alg (5 or 8%). The value of ΔC (difference between the maximum (C) and pre-feeding (C) blood glucose levels) was significantly reduced in both Ca-Alg groups, and the area under the blood glucose level-time curve over 120 min (ΔAUC, with C as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…21) Moreover, we found that Ca-Alg suppressed the elevation of blood glucose levels after ingestion of starch in rats and humans by inhibiting the degradation of maltose to glucose by α-glucosidase. 22,23) Moreover, we reported the blood Cho-lowering effect of Ca-Alg in rats. 24) Ca-Alg adsorbs bile acids in the intestine, inhibiting their reabsorption and enterohepatic circulation, and thus decreasing bile acid levels in the blood and enhancing their fecal excretion.…”
Section: Introductionmentioning
confidence: 92%
“…21) Moreover, we found that Ca-Alg suppressed the elevation of blood glucose levels after ingestion of starch in rats and humans by inhibiting the degradation of maltose to glucose by α-glucosidase. 22,23) Moreover, we reported the blood Cho-lowering effect of Ca-Alg in rats. 24) Ca-Alg adsorbs bile acids in the intestine, inhibiting their reabsorption and enterohepatic circulation, and thus decreasing bile acid levels in the blood and enhancing their fecal excretion.…”
Section: Introductionmentioning
confidence: 92%
“…1). This review included 18 RCTs, from which 12 had a crossover design [27][28][29][30][31][32][33][34][35][36][37][38] and 6 had a parallel design. [39][40][41][42] Of the 18 studies, 10 28,29,32-35 involved an acute intervention as an oral glucose tolerance test (OGTT), measuring the intervention's effect on PPG over 2 to 3 h. Five studies 27,30,[40][41][42] conducted only long-term interventions analyzing the effect on FPG.…”
Section: Resultsmentioning
confidence: 99%
“…In all the included studies, a placebo was used as a control comparator (Table 2). [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] The study populations ranged from 12 to 97 participants. Ten studies [29][30][31][32][33][34][35][36][37][38] were conducted on healthy participants (n ¼ 256) with a normal FPG (<100 mg/dL) and BMI (18.5 and 24.9 kg/m 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further, Ca-Alg moderated the postprandial increase of blood glucose level in rats and humans. Ca-Alg has been confirmed as safe for use as a food additive, and is superior to Na-Alg, because there is no risk of hypertension Changes in blood glucose level (ΔC) after eating test noodles to volunteers [30]. The data represent means ± S.D., n = 15.…”
Section: Resultsmentioning
confidence: 99%
“…Diabetics may develop serious complications such as retinopathy, nephropathy and neuropathy, in addition to myocardial infarction, cerebral infarction and so on [27,30], even though the initial subjective symptoms may be minor. Ca-Alg is known to suppress the postprandial increase of blood glucose, and therefore may be helpful in preventing lifestyle-related diseases such as diabetes.…”
Section: Suppression Of Postprandial Blood Glucose Levelmentioning
confidence: 99%